Clinical management of diabetic ketoacidosis - Asrar Rashid; Sanjay Perkar; Praveen Khilnani; Sarah Ehtisham (Wolters Kluwer Medknow Publications, 2017)
Diabetic Ketoacidosis (DKA) is a commonly seen condition in Pediatric age group requiring admission to the PICU. The scope of this article is to discuss the management of children with moderate to severe DKA requiring hospital- ization. Electrolyte disturbances such as hypoglycemia, hypokalemia, hypocalcemia, hypomagnesemia and severe hypophosphatemia can occur during the clinical course of DKA. Additionally, DKA can be associated with sepsis with serum C-reactive protein and interleukin-6 levels being useful in excluding an underlying infection, as well as confirming and monitoring sepsis. DKA can result in serious morbidity such as cerebral edema, cerebral infarction, venous and arterial stroke. Simultaneous pulmonary and cerebral edema with multiple CNS infarctions as a complication of DKA has also been described. Severe DKA can lead to cardiac failure, pulmonary edema and spinal cord edema resulting in tetraplegia. Current review emphasizes mainly regarding all the measures to reduce morbidity and potential mortality. To minimize morbidity, early recognition of diabetes is paramount especially when polyuria, polydipsia, lethargy and weight loss is described. The clinical suspicion of DKA should be confirmed quickly by biochemical evidence and appropriate treatment instituted. The International Society of Pediatric Diabetes introduced guidelines (ISPAD 2014) as well as British Society of Pediatric Endocrinology are also discussed to put it in clinical perspective.